PENGARUH MANAJEMEN GURU TERHADAP PRESTASI BELAJAR SISWA - Raodah Muchlis; Dewi Furwana; A. Riawarda (Kelola: Journal of Islamic Education Management, 2022)
This study aims to: 1)determine the management of teachers in SMP Negeri 5 Palopo, 2)determine student achievement in SMP Negeri 5 Palopo and 3)determine the effect of teacher management on student achievement in SMP Negeri 5 Palopo. This study uses quantitative research methods with ex-post fact research design. The total population is all teachers of SMP Negeri 5 Palopo which consists of civil servants and honorary teachers totaling 33 people with sampling using saturated sampling technique, So the sample used is 30 people. This research instrument uses questionnaires and documentation while statistical analysis techniques are used to manage the result data, namely descriptive statistical analysis and inferential analysis using a simple linear regression equation Y = a + bx with the help of SPSS vers.20 for windows. Based on the results of this research show that teacher management at SMP Negeri 5 Palopo is included in the good category with a percentage of 73%. Meanwhile, student achievement at SMP Negeri 5 Palopo is in the good category with a percentage of 58%. In addition, obtained T count 26,812 > T table 1,697 so that it can be concluded that X has an effect on Y with R2 (R square) of 0.963 or 96.3% positive influence on student achievement at SMP Negeri 5 Palopo while the remaining 3.7% is influenced by variables which cannot be explained in this study.